Pemeliharaan dan Pelatihan Troubleshoot Jaringan Komputer untuk Peningkatan Layanan Akademik Universitas Jambi - Sahrial; Arsa, Daniel; Utomo, Pradita Eko Prasetyo; Suprayogi, Dawam; Ilhami, Mohamad (Fakultas Sains dan Teknologi, Universitas Jambi, 2025)
ICT (Information and Communication Technology) infrastructure and networks are essential components in supporting the success of an organization. In today's digital era, ICT infrastructure and networks are key in facilitating communication and collaboration, managing data, optimizing operational efficiency, and increasing organizational innovation capabilities. Therefore, investment in ICT infrastructure and networks is significant in strengthening the competitiveness and sustainability of organizations in the current digital era. This investment may be related to routine maintenance and training for related human resources. To support academic and operational activities at the Faculty of Science and Technology and Institute for Research and Community Services (LPPM) Universitas Jambi, it is necessary to carry out comprehensive computer and internet network maintenance activities at these two locations. Then, it is also necessary to carry out more intensive training for the assigned Engineer on-site to handle basic computer network problems (troubleshooting).